1947
DOI: 10.1103/physrev.72.931
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radiocarbon from Cosmic Radiation

Abstract: C 14 produced by the N u (n, p) reaction of cosmic-ray neutrons has been detected and identified. The C 14 concentration of biological methane was enriched by factors of up to 260-fold by thermal diffusion to raise the activity to convenient levels for counting. The pure methane was used as the filling gas in large Geiger-Mtiller counters.The activity in biological methane was found to be 10.5 disintegrations per minute per gram C, or 0.95 X10~1 2 gram C 14 per gram C. This is in reasonable agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(34 citation statements)
references
References 17 publications
(1 reference statement)
0
30
0
3
Order By: Relevance
“…This typically applies only to carbon in fossil reservoirs, as other carbon reservoirs are continuously supplied with fresh 14 C from exchange with the atmosphere where 14 CO 2 is produced in the stratosphere and upper troposphere (Libby, 1946;Anderson et al, 1947). In the natural carbon balance this 14 C would cycle through the atmospheric, biospheric, and oceanic reservoir until it decays.…”
Section: Bozhinova Et Al: Modeling 14 Co 2 For Western Europementioning
confidence: 99%
See 1 more Smart Citation
“…This typically applies only to carbon in fossil reservoirs, as other carbon reservoirs are continuously supplied with fresh 14 C from exchange with the atmosphere where 14 CO 2 is produced in the stratosphere and upper troposphere (Libby, 1946;Anderson et al, 1947). In the natural carbon balance this 14 C would cycle through the atmospheric, biospheric, and oceanic reservoir until it decays.…”
Section: Bozhinova Et Al: Modeling 14 Co 2 For Western Europementioning
confidence: 99%
“…For example, interpretation of 14 C in air samples from aircraft requires detailed dispersion modeling of surface emissions into a highly dynamic atmosphere, while interpretation of monthly integrated air samples from tall towers requires the inclusion of the re-emergence of old 14 C signals after longer turn-over in the oceans and biosphere. In a recent publication (Bozhinova et al, 2013), we showed that the interpretation of growing season integrated plant samples additionally requires simulation of location and weather dependent photosynthetic uptake and plant development patterns. A successful 14 C monitoring strategy will thus depend D. Bozhinova et al: Modeling 14 CO 2 for Western Europe 7275 strongly on our ability to capture these diverse processes on diverse scales.…”
Section: Bozhinova Et Al: Modeling 14 Co 2 For Western Europementioning
confidence: 99%
“…Radiocarbon ( 14 C) is produced in the earth's atmosphere by the capture of slow cosmic ray neutrons by the atmospheric 14 N nuclei. This was the first cosmic-ray-produced isotope to be discovered in 1947, in an experiment using sewage methane (Anderson et al 1947). Soon thereafter, it was applied to archaeological/anthropological dating (Libby et al 1949;Libby 1952).…”
Section: -The Authors With Apologies To G Orwellmentioning
confidence: 99%
“…When one or more isotopes of an element are daughter nuclides of a radioactive decay, the isotope ratio(s) of the element depend on the original concentration of the mother nuclide in the sample and the time. The natural radioactivity is, e.g., used for dating via the half-life in archaeometry (e.g., radiocarbon dating) [104][105][106] and geochronology (e.g., U-Pb dating) [107][108][109] or for using the isotopic variation as natural fingerprint (e.g., Sr, Pb). [110][111][112][113] The second effect derives from simple mass-dependent thermodynamic processes (e.g., evaporation), simply influenced by preferential diffusion of lighter isotopes.…”
Section: Mass Fractionation Effects and Isotopic Variationsmentioning
confidence: 99%